Direct oxidation of H-2 to H2O2 over Pd-based catalysts: influence of oxidation state, support and metal additives - Choudhary, Vasant R.; Samanta, C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
The influence of oxidation state (reduced and oxidized), support (ZrO2, Ga2O3, CeO2, SiO2, H-beta, ThO2, CeO2-ZrO2, BPO4 and Pd/Al2O3) and precious metal additives (Au, Pt, Rh and Ru) on the direct H2O2 synthesis has been investigated over Pd-based catalysts. For all the supports investigated herein, the oxidized Pd catalysts showed significantly superior H2O2 yields as compared to their reduced counterparts. The effect of the Pd oxidation state was found to be more important for determining the H2O2 yields than the particle size and surface area properties of the catalyst system. An excellent correlation was observed between the H2O2 selectivity and H2O2 decomposition activity of the oxidized Pd catalysts. The oxidized Pd catalysts showed almost an order of magnitude lower H2O2 decomposition activity than the reduced catalysts. The H2O2 yield in the H-2 to H2O2 oxidation passed through a maximum with increase in the An concentration. Although a similar effect was also observed in case of Pt, Au was found to be a superior promoter for the direct H2O2 synthesis process. Addition of Rh and Ru was found to be detrimental for the H2O2 yields; these results can be explained in terms of increased H2O2 decomposition activity and/or enhanced H-2 to H2O reaction activity in their presence. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: decomposition; direct synthesis; H2O2; metal additives; oxidation state; Pd catalysts; supports

Tethered Pd-complex on solid support: catalyst for acid-free carbonylation reactions - Sarkar, Bibbas R.; Mukhopadhyay, Kausik; Chaudhari, Raghunath V. (Catalysis Communictions, 2007)
{Palladium complex [
Keywords: decomposition; direct H2O2 synthesis; halides; Promoter

Au based Ni and Co bimetallic core shell nanocatalysts for room temperature selective decomposition of hydrous hydrazine to hydrogen - Jain, P.; Anila, K. A.; Vinod, C. P. (ChemistrySelect, 2019)
Nickel and Cobalt bimetallic catalysts with Au as core metal has been synthesized and demonstrated for hydrazine decomposition reaction for producing hydrogen. Gold-cobalt and gold nickel bimetallic system belonging to the class of strained structures with high lattice mismatch of approximately 14% are demonstrated for synergistic effects atypical of monometallic counterparts for the selective decomposition of hydrous hydrazine to H-2 with N-2 as the other product at room temperature.
Keywords: (HDR); Au@Co.; Au@Ni.; Bimetallic; catalyst.; core; decomposition; Hydrazine; nanoparticles.; reaction; shell

Comparison of different water models for melting point calculation of methane hydrate using molecular dynamics simulations - Choudhary, Nilesh; Chakrabarty, Suman; Roy, Sudip; Kumar, Rajnish (Chemical Physics, 2019)
Molecular dynamics simulation is a powerful tool to understand the gas hydrate nucleation, growth, and dissociation at molecular level. Prerequisite of super-cooling during gas hydrate formation and a certain degree of super-healing during melting shows significant hysteresis in the transition between solid and liquid state due to large nucleation barrier. Different water models quantitatively differ in their prediction of thermodynamic and kinetic properties of bulk water, including phase behaviour. The present work carries out a systematic investigation of the effect of the chosen water model on the phase behaviour, in particular, the decomposition of methane hydrate. Void-induced melting has been used to predict the melting point of methane hydrate using TIP4P/Ice, TIP4P/2005, TIP4P, and SPC/E water models. This method avoids the need for a predetermined interface for melting point calculations and thus may have its importance in identifying dissociation kinetics of bulk hydrate.
Keywords: decomposition; Gas hydrates; Void-induced melting; Water models